Factors influencing the intention to adopt halal logistics services among halal SMEs in Malaysia - Illyas Tan, Mohd. Iskandar (2015)
This study was aim to understand the influence of adoption factors on the intention of adopting an innovation (Halal Logistics) among Malaysian Halal SMEs. This re search employed a quantitative research design using survey research method. Four objectives were established. The first is to formulate a model that identifies the influence of adoption factors on innovation (Halal Logistics) adoption intention among Malaysian Halal SMEs. This was achieved through literature reviews and preliminary study. Five halal compliant logistics service providers (LSPs) were contacted through phone and email correspondences. Seven research hypotheses were derived and seven factors that influenced the innovation (Halal Logistics) adoption intention were identified: the presence of familiarity with innovation, status characteristics, position in social network as internal factors as well as benefit, geographical setting, societal culture and political condition as external factors. The second objective is to develop an instrument that can be used to measure the influence of adoption factors on adoption intention among Halal SMEs.